Joint Effect of Beer, Spirits Intake, and Excess Adiposity on Hyperuricemia Among Chinese Male Adults: Evidence From the China National Health Survey - He, Huijing; Pan, Li; Ren, Xiaolan; Wang, Dingming; Du, Jianwei; Cui, Ze; Zhao, Jingbo; Wang, Hailing; Wang, Xianghua; Liu, Feng; Pa, Lize; Peng, Xia; et al. (Frontiers in Nutrition, 2022)
Alcohol intake and excess adiposity are associated with serum uric acid, but their interaction effect on hyperuricemia is still unclear. Using data from the China National Health Survey (CNHS) (2012-2017), we analyzed the additive interaction between beer, spirits intake, excess adiposity (measured by body mass index (BMI), body fat percentage (BFP), visceral fat index (VFI)) and hyperuricemia among male participants aged 20-80 in mainland China. Relative excess risk due to interaction (RERI), the attributable proportion due to interaction (AP), and the synergy index (SI) were calculated to assess the interaction effect on the additive scale. RERI and AP larger than 0, SI large than 1 indicate positive additive interaction effect. Among the 12592 male participants, the mean serum uric acid level was (367.185.5) mol/L, and 24.1% were hyperuricemia. Overweight/obese men who currently drank spirits had an odds ratio (OR) of 3.20(95%CI: 2.71-3.79) than never drink group, with RERI, AP and SI of 0.45(95%CI: 0.08-0.81), 0.14(95%CI: 0.03-0.25), and 1.25(95%CI: 1.02-1.54), respectively. However, although combined exposures on beer intake and excess adiposity had the highest OR comparing with no beer intake and non-obese participants, there was no additive interactive effect, with RERI, AP and SI in the overweight/obesity & beer intake group of 0.58(-0.41 to 1.57), 0.17(-0.08 to 0.41) and 1.30(0.85-1.97), respectively. Other excess adiposity indexes revealed similar estimates. Our results suggest that the exposures of both excess adiposity and alcohol drink result in an additive interaction effect on hyperuricemia: combined risk of excess adiposity with spirits intake, but not beer, was greater than the sum of the effects among Chinese male adults.